2014
DOI: 10.1101/gr.172809.114
|View full text |Cite
|
Sign up to set email alerts
|

Loss of transcriptional control over endogenous retroelements during reprogramming to pluripotency

Abstract: Endogenous retroelements (EREs) account for about half of the mouse or human genome, and their potential as insertional mutagens and transcriptional perturbators is suppressed by early embryonic epigenetic silencing. Here, we asked how ERE control is maintained during the generation of induced pluripotent stem cells (iPSCs), as this procedure involves profound epigenetic remodeling. We found that all EREs tested were markedly up-regulated during the reprogramming of either mouse embryonic fibroblasts, human CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 49 publications
(63 reference statements)
6
105
0
1
Order By: Relevance
“…Finally, RNA-Seq expression of HEMO was analyzed in the reprogramming experiments of differentiated somatic cells into iPSCs described in ref. 32, and hits reported in Fig. 7A, Right highlight the specific reprogramming of the HEMO gene-not observed with env-W and env-FRD-which parallels the expected profile of expression of the OCT4/ POU5F1 transcription factor.…”
Section: Syn-car1mentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, RNA-Seq expression of HEMO was analyzed in the reprogramming experiments of differentiated somatic cells into iPSCs described in ref. 32, and hits reported in Fig. 7A, Right highlight the specific reprogramming of the HEMO gene-not observed with env-W and env-FRD-which parallels the expected profile of expression of the OCT4/ POU5F1 transcription factor.…”
Section: Syn-car1mentioning
confidence: 85%
“…To get insight into the possible involvement of HEMO in embryonic development, we further analyzed by data mining a series of human RNA sequencing (RNA-Seq) experiments deposited at the Sequence Read Archive National Center for Biotechnology Information platform corresponding to different stages of development (29)(30)(31)(32). Extraction of the expression profiles of a set of human genes was performed, and the results are illustrated in Fig.…”
Section: Syn-car1mentioning
confidence: 99%
“…Another study showed that a small portion of mouse ESCs and iPSCs express ERV-L retroviruses and possess the ability to differentiate not only into embryonic lineages but also into extraembryonic cells (30). Recently, Friedli et al showed that aberrant activation of intracisternal A particle, a member of ERV-K, occurred during reprogramming of mouse embryonic fibroblasts toward iPSCs, as well as HERV-H behavior in a human case, which may suggest the importance of ERV activity in reprogramming beyond species (31). An important future task will involve examining the roles of speciesspecific ERVs in reprogramming and pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study has shown that ∼40% of 3771 human endogenous retroviruses type-H (HERV-Hs) transcripts, which are detected in both human pluripotent stem cells and mesendodermal cells, are transiently hyper-activated during reprogramming (Friedli et al, 2014;Lu et al, 2014;Ohnuki et al, 2014;Wang et al, 2014). Furthermore, human ESCs and iPSCs expressing aberrantly high levels of HERV-H transcripts show defective directed differentiation down the neural lineage (Koyanagi-Aoi et al, 2013; Ohnuki et al, 2014).…”
Section: Transient Expression Of Developmental Genes During Reprogrammentioning
confidence: 99%